Use of coffee flower as a novel resource for the production of bioactive compounds, melanoidins, and bio-sugars. (30th November 2019) - Nguyen, Thi Minh Thu; Cho, Eun Jin; Song, Younho; Oh, Chi Hoon; Funada, Ryo; Bae, Hyeun-Jong
Highlights: Pressurized hot water extraction is an effective method for biomolecules extraction. Caffeine and trigonelline are major compounds in coffee flower. Enzymatic hydrolysis enhances bio-sugar convention. A novel approach using coffee flower for producing high value-products. Abstract: Although coffee beans have been widely studied, application of coffee flower (CF) has not been previously investigated. Here, we evaluated the use of CF for the production of bioactive compounds, melanoidins, and bio-sugars through the green process. Pressurized hot water extraction was found to be the most appropriate method for extracting bioactive compounds from CF, which contain high values of total phenolic content and have antioxidant properties. Caffeine and trigonelline were the main compounds in CF with yields of 1070.8 mg and 1092.8 mg/100 g dry weight (DW), respectively. Melanoidins were also identified and quantified in the CF extracts that is approximately 30.2% were efficiently recovered in the initial extracts of CF. Bio-sugar was also obtained from cellulase and pectinase at a 92.8% conversion rate. The aim of this study is to promote a novel approach using high amounts of CFs in the production of functional healthy foods and beverages.